Evaluation of Condition of Meat Shop on Prospective of Meat Act in Madi Municipality, Chitwan, Nepal - Bastakoti, R; Upadhyaya, S (Nepalese Veterinary Journal, 2023)
There are many meat shop around the country and only few are maintaining standard according to animal slaughter house and meat inspection act, 2057. We are trying to evaluate standard of 122 meat shop of Madi Municipality. We have prepared a questionnaire and surveyed all the meat shop to know the condition of shop and their standard with reference to animal slaughter house and meat inspection act, 2057. Meat shop in Madi is dominated by chicken, 85.71%. Which are equipped with D-freeze (60.65%) for freezing meat for a day with 91.22% having backup support for freezers. 70.08% of the shops are registered as mentioned by act. Similarly, only few (7.09%) of the shop have area met the requirement given by act. Ventilation in 59.02% of the shops are perfectly in line with act whereas tiles in the floor was absent in 83.61% of the shops. Good water supply and Slab in butchering area is in minimal with 8.20% and 4.10% respectively. Good condition mesh wire is present in order to prevent flies in 19.67% of the shops. Furthermore, only 1.64% of the butcher are aware about rules and regulations and 11.48% of the shop uses proper disinfection. Similarly, waste management is mostly done by making manure (28.69%) followed by burning (27.05%). Additionally, consumer’s preference is in fresh meat (79.51%) among which demand of chest meat is higher (52.46%) in chicken meat. In conclusion, most of the butcher are unaware of act and are doing their business without any knowledge of act and are not in line with the instructions given by the act.